2013
DOI: 10.1038/pr.2013.217
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative modeling of clinical, cellular, and extracellular matrix variables suggest prognostic indicators in cancer: a model in neuroblastoma

Abstract: Background: Risk classification and treatment stratification for cancer patients is restricted by our incomplete picture of the complex and unknown interactions between the patient's organism and tumor tissues (transformed cells supported by tumor stroma). Moreover, all clinical factors and laboratory studies used to indicate treatment effectiveness and outcomes are by their nature a simplification of the biological system of cancer, and cannot yet incorporate all possible prognostic indicators. Methods: A mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…Images were acquired using Olympus BX51 light microscope with CCD Olympus DP50 camera along with the CellA Analysis Image Processing Program. Ki67 index was calculated by automatic quantification using the Image Pro‐Plus software as described previously . Neural cell adhesion molecule (NCAM) positive metastatic cells in liver, lungs and bone marrow were manually quantified in 1–2 entire tissue sections/mouse at ×20 magnification.…”
Section: Methodsmentioning
confidence: 99%
“…Images were acquired using Olympus BX51 light microscope with CCD Olympus DP50 camera along with the CellA Analysis Image Processing Program. Ki67 index was calculated by automatic quantification using the Image Pro‐Plus software as described previously . Neural cell adhesion molecule (NCAM) positive metastatic cells in liver, lungs and bone marrow were manually quantified in 1–2 entire tissue sections/mouse at ×20 magnification.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis of the quantitative data of fibers, GAGs, tumor cells, and immune system markers compared with the current parameters used to predict risk of relapse (stage, age, histopathology, state of MYCN oncogene, state of 11q region, overall genomic profile, and ploidy) (7274) and other genetic markers of prognostic interest in a subset of 78 primary neuroblastic tumors has already been published by our group, and highlights the interest of studying ECM in neuroblastic tumors (50). The fact that ECM elements differ depending on the characteristics of the tumors and, more interestingly, the fact that the characteristics of ECM elements are related to prognosis (relapse or overall survival) advocates on behalf of the regulatory role of ECM biotensegrity in tumor progression.…”
Section: Evidences Of Ecm Biotensegrity Changes In Malignant Tissuementioning
confidence: 96%
“…In fact, the dynamic mechanical balance achieved through mechanosensors, cytoskeletal tensegrity, molecular biotensegral intra-cellular pathways, ECM with compressive and resistant elements, supportive cells (such as fibroblasts and multiple tumor-associated immune cells), and vascular and lymphatic vessels tensional structures, can be as important as the genetic instability of tumor cells in the pathogenesis and evolution of the malignant process (42, 49). In this regard, various studies have demonstrated the importance of cell–ECM biotensegrity in cancer (34, 48, 50). Indeed, a desmoplastic reaction is frequent in many solid tumors, such as breast, prostate, colon, or lung, in which high levels of TGF-b and PDGF are found.…”
Section: Cell and Tissue Biotensegrity In Cancermentioning
confidence: 99%
See 2 more Smart Citations